THE PSYCHOSOCIAL MEDIATING DIMENSIONS OF THE ILLNESS BEHAVIOUR AND QUALITY OF LIFE IN GERIATRIC POPULATION - Nieto Munuera, Joaquín; Abad Mateo, Mª Ángeles; Torres Ortuño, Ana (Anales de Psicología / Annals of Psychology, 1998)
We present a review of the main findings in several works about geriatric population, extracted from our studies. The objetives are focused in studying psychosocial variables that influence the behavior of the elderly people in health and illness, and the consecquences in quality of life. We discuss the presence of different behavior patterns in response to the illness, influenced as much as for psychological and sociodemographic variables..